PERENCANAAN PENERANGAN JALAN UMUM (PJU) TENAGA SURYA PADA DESA SIKEBEN KECAMATAN SIBOLANGIT KABUPATEN DELI SERDANG - Barus, Khairul Imam; Lesmana, Dicky; Sutejo, Eddy (Power Elektronik : Jurnal Orang Elektro, 2024)
Solar energy is a renewable energy source (EBT) that will never run out. One utilization of solar energy is as a source of solar-powered public street lighting (PJUTS). Public street lighting aims to assist the public when traveling and improve road safety at night. This research will focus on planning solar-powered public street lighting located in Sikeben Village, Sibolangit District, Deli Serdang Regency, which is a provincial road with a width of 5 meters and a length of 3950 meters. At night, several points on the road have minimal lighting, potentially increasing the risk of accidents and crime. Additionally, at some other points, lighting is already installed, but it still relies on the PLN (State Electricity Company) as the power source.The planning of solar-powered public street lighting (PJUTS) requires 158 lighting points with 24 Watt LED lamp loads. With a pole height of 7 meters and a distance of 25 meters between poles, the lighting intensity is calculated to be 6.72 lux manually. According to applicable standards, the value of illumination intensity is 3-7 lux. The solar modules used have a capacity of 75 Wp. PJUTS operates for 12 hours a day and can continue operating for 3 days without solar energy source. The total cost for this solar-powered public street lighting is Rp 1,224,500,000.